The subnivium: a deteriorating seasonal refugium. Issue 5 (1st June 2013) - Pauli, Jonathan N; Zuckerberg, Benjamin; Whiteman, John P; Porter, Warren
Abstract : For many terrestrial organisms in the Northern Hemisphere, winter is a period of resource scarcity and energy deficits, survivable only because a seasonal refugium – the "subnivium" – exists beneath the snow. The warmer and more stable conditions within the subnivium are principally driven by snow duration, density, and depth. In temperate regions, the subnivium is important for the overwintering success of plants and animals, yet winter conditions are changing rapidly worldwide. Throughout the Northern Hemisphere, the impacts of climate change are predicted to be most prominent during the winter months, resulting in a shorter snow season and decreased snow depth. These climatic changes will likely modify the defining qualities of the subnivium, resulting in broad‐scale shifts in distributions of species that are dependent on these refugia. Resultant changes to the subnivium, however, will be spatially and temporally variable. We believe that ecologists and managers are overlooking this widespread, crucial, and vulnerable seasonal refugium, which is rapidly deteriorating due to global climate change.